A Comprehensive Understanding of the Aging Effects of Extreme Fast Charging on High Ni NMC Cathode. Issue 22 (22nd April 2022) - Tanim, Tanvir R.; Yang, Zhenzhen; Finegan, Donal P.; Chinnam, Parameswara R.; Lin, Yulin; Weddle, Peter J.; Bloom, Ira; Colclasure, Andrew M.; Dufek, Eric J.; Wen, Jianguo; Tsai, Yifen; Evans, Michael C.; et al.
Abstract: As the battery industry shifts toward high Ni content cathodes, such as LiNi0.8 Mn0.1 Co0.1 O2 [NMC811], a complete understanding of the degradation mechanisms of NMC811 under extreme fast charging (XFC) (XFC, ≤10–15 min charging) conditions is needed. Such comprehensive understanding would identify the most critical materials gaps that need to be addressed for enabling XFC long‐life cells for electric vehicles. This study maps out the key aging mechanisms for NMC811 cycled at different XFC conditions (between 1C and 9C) for up to 1000 cycles. To acquire a fundamental understanding of utilization and degradation, cells are evaluated using a range of electrochemical techniques, and multimodal and multiscale microscopy techniques to quantify chemical, structural, and crystallographic degradation as a function of cycling conditions for the NMC cathode. When comparing NMC811 to NMC532, it is observed that NMC811 has a greater subsurface crystallographic degradation and displays a similar magnitude of subparticle cracking. However, the NMC811 maintains superior performance despite those advanced degradations. The superior cycle life performance is attributed to the NMC811 particles having radially oriented grains and improved transport properties. NMC811 shows between 4.6× and 3.15× reduction in capacity fade than NMC532 for charging rates between 4C (e.g., 15‐min charging) and 6C (10‐min charging). Abstract : A comprehensive understanding of the aging mechanisms of NMC‐cathodes under extreme fast‐charging, identifies key R&D gaps and research pathways.